Developing BMT as a loss-profit sharing-based microfinance: an Indonesian experience - Husni Mubarrak (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2018)
This article would like to discuss an Indonesian experience in developing Baitul Mal wat Tamwil (BMT) since 1990’s as an alternative microfinance which based on loss and profit sharing schema that realized a more just economic system. This research is conducted by both bibliographical overviews and empirical investigations. This paper would like to elaborate more on how BMT developed and maintained its capacity and efforts, in providing a more just alternative model instead of interest system which had shown negative spread and pseudo economic growth. This, however, requires emphasizing the main differences between both systems (sharing and interest). It also discusses on how BMT upgraded competitively various attractive products which based on loss and profit sharing. The establishment of BMT in Indonesia could not be separated from the emergence of “creative minority” and “enlightened group” in some campuses in Indonesia to build BMT since 1984, which later followed and developed by Indonesian Muslim Intellectual Association (Ikatan Cendekiawan Muslim Indonesia/ ICMI) since 1991. The research findings showed that the schema which is used by BMT on loss and profit sharing is a real practical effort which then has successfully developed, massively contributed and largely triggered Indonesian economic in the real sector, especially for the small and medium economic scale enterprises (SMES) in order to poverty alleviation. It also reflected as an experiment of early steps in recognizing Islamic economy in Indonesia. BMT also still could survive, even when a huge economic crisis struck Indonesia particularly and South East Asia generally in 1997.